2022
DOI: 10.3847/1538-4365/ac5f59
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR Observations of 52 Compton-thick Active Galactic Nuclei Selected by the Swift/Burst Alert Telescope All-sky Hard X-Ray Survey

Abstract: We present systematic broadband X-ray spectral analysis of 52 Compton-thick ( 24 ≤ log N H LOS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 105 publications
4
17
0
Order By: Relevance
“…Our large data set is able to break the degeneracy model and show that a solution like the one found in Marchesi et al (2019) is preferred, in where our photon index and average N H are in perfect agreement within errors. Our best-fit values are also in accordance, within errors, with the ones reported by Tanimoto et al (2022), where one NuSTAR and one XMM-Newton observation, as well as Swift/ XRT data are fitted using the XClumpy code (Tanimoto et al 2019). They find G = -+ 1.88 0.16 0.12 and an average hydrogen column density of = -+ N 15.3 10 H,av 3.25 13.5 24 cm −2 , both in agreement with our results.…”
Section: Comparison With Previous Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our large data set is able to break the degeneracy model and show that a solution like the one found in Marchesi et al (2019) is preferred, in where our photon index and average N H are in perfect agreement within errors. Our best-fit values are also in accordance, within errors, with the ones reported by Tanimoto et al (2022), where one NuSTAR and one XMM-Newton observation, as well as Swift/ XRT data are fitted using the XClumpy code (Tanimoto et al 2019). They find G = -+ 1.88 0.16 0.12 and an average hydrogen column density of = -+ N 15.3 10 H,av 3.25 13.5 24 cm −2 , both in agreement with our results.…”
Section: Comparison With Previous Resultssupporting
confidence: 92%
“…This leads us to the computation of an Eddington ratio range of λ Edd = 0.03-0.05, where λ Edd = L Bol /L Edd . This result is in agreement with the value found by Tanimoto et al (2022) of λ Edd = 0.037.…”
Section: Bolometric Luminosity Smbh Mass and Eddington Ratiosupporting
confidence: 93%
“…The all-sky Swift/BAT survey, in particular, has detected ∼1100 AGNs in the 14-195 keV band (Oh et al 2018). X-ray follow-up of BAT-detected sources showed that a significant fraction (∼20%-30%) of local AGNs are obscured by Compton-thick material (CT, ( ) N log cm H 2 - 24; e.g., Burlon et al 2011;Ricci et al 2015;Akylas et al 2016;Marchesi et al 2018;Torres-Albà et al 2021;Tanimoto et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A key component to understanding the AGN feeding mechanism is the so-called "torus" (e.g., Urry & Padovani 1995;Almeida & Ricci 2017), which is considered the fuel reservoir of the SMBH. The spectral signatures of the X-ray radiation absorbed and/or reprocessed by the torus can provide constraints on its covering fraction and column density (e.g., Kawamuro et al 2016;Tanimoto et al 2020;Toba et al 2020;Uematsu et al 2021;Tanimoto et al 2022).…”
Section: Introductionmentioning
confidence: 99%